2011
DOI: 10.5194/acp-11-655-2011
|View full text |Cite
|
Sign up to set email alerts
|

Solid state and sub-cooled liquid vapour pressures of cyclic aliphatic dicarboxylic acids

Abstract: Abstract. Knudsen Effusion Mass Spectrometry (KEMS)has been used to measure for the first time the solid state vapour pressures of a series of aliphatic cyclic dicarboxylic acids with increasing ring size. Additionally the atmospherically important compounds; cis-pinonic acid and levoglucosan were also measured. Differential Scanning Calorimetry (DSC) was used to measure melting points, enthalpies and entropies of fusion, which were used to determine sub-cooled liquid vapour pressures for the compounds. The su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 45 publications
5
58
0
Order By: Relevance
“…Further vapour pressures and enthalpies and entropies of sublimation have been reported for the substituted dicarboxylic acids 2-methyl-and 2-hydroxy-malonic acid, 2-methyl-, 2-methyl-1,2-hydroxy-, 2-hydroxy-, 2,3-dihydroxy-, 2-amino-and 2-keto-succinic acid, 2-methyl-, 3-methyl-, 3-carboxylic-3-hydroxy-, 2-amino-, 2-keto-and 3-keto-glutaric acid (Booth et al, 2010). Similarly, measurements of cyclic aliphatic compounds (1,1-cyclopropane-, 1,1-cyclobutane-, 1,2-cyclopentane-and 1,3-and 1,4-cyclohexane-dicarboxylic acids, levoglucosan and cis-pinonic acid; Booth et al, 2011b) and mono-and di-substituted aromatic compound (phthalic-, isophthalic-, terephthalic-, vanillic-, syringic-and p-anisic acids and nitrocatechol) vapour pressures and enthalpies of sublimation have been made (Booth et al, 2011a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further vapour pressures and enthalpies and entropies of sublimation have been reported for the substituted dicarboxylic acids 2-methyl-and 2-hydroxy-malonic acid, 2-methyl-, 2-methyl-1,2-hydroxy-, 2-hydroxy-, 2,3-dihydroxy-, 2-amino-and 2-keto-succinic acid, 2-methyl-, 3-methyl-, 3-carboxylic-3-hydroxy-, 2-amino-, 2-keto-and 3-keto-glutaric acid (Booth et al, 2010). Similarly, measurements of cyclic aliphatic compounds (1,1-cyclopropane-, 1,1-cyclobutane-, 1,2-cyclopentane-and 1,3-and 1,4-cyclohexane-dicarboxylic acids, levoglucosan and cis-pinonic acid; Booth et al, 2011b) and mono-and di-substituted aromatic compound (phthalic-, isophthalic-, terephthalic-, vanillic-, syringic-and p-anisic acids and nitrocatechol) vapour pressures and enthalpies of sublimation have been made (Booth et al, 2011a).…”
Section: Methodsmentioning
confidence: 99%
“…Main computational methods used in EUCAARI (large scale). In-situ Booth et al (2009Booth et al ( , 2010Booth et al ( , 2011a The ageing of BSOA from typical Boreal forest emissions during a day-night-day cycle in the SAPHIR chamber was correlated to the OH dose. Ageing was manifested as a distinctive increase of the O/C ratio in the particles and a change in the condensation growth of the particles, indicating the photo-chemical formation of condensible material.…”
Section: Appendix Amentioning
confidence: 99%
“…The low vapour pressure of levoglucosan (Oja and Suuberg, 1999;Booth et al, 2011) as well as the minor impact of temperature on the observed volatility of levoglucosan in ambient PM (Ruehl et al, 2011) further supports its stability and thus its suitability as a tracer species. Recent investigations on the stability of levoglucosan in aqueous solution suggest that "oxidation of levoglu-cosan in atmospheric deliquescent particles is at least as fast as that of other atmospherically relevant organic compounds and levoglucosan may not be as stable as previously thought in the atmosphere, especially under high relative humidity conditions" (Hoffmann et al, 2010;Teraji and Arakaki, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…The impact of the abovementioned effects on the levoglucosan content in the (true) ambient aerosol still remains to be documented; however, these are indications that levoglucosan may be depleted in the atmosphere, and that possible degradation should thus be taken into account when using levoglucosan as a tracer of BB emissions in source apportionment studies. Nonetheless, levoglucosan is a valuable tracer to investigate the impact of residential wood burning in urban (Oliveira et al, 2007;Timonen et al, 2008;Caseiro et al, 2009;Szidat et al, 2009;Bari et al, 2010;Schnelle-Kreis et al, 2010;Saffari et al, 2013), rural background Puxbaum et al, 2007, van Drooge andBallesta, 2009) and remote areas (May et al, 2009;Yttri et al, 2014), especially during winter, when wood combustion is used for domestic heating.…”
Section: Introductionmentioning
confidence: 99%
“…Note that (b) excludes the outlier value from Cappa et al (2007). Plotted literature data (letters) correspond to sources as follows: A (Bilde et al 2003), B (Booth et al 2009), C (Booth et al 2010), D (Booth et al 2011), E (Cappa et al 2007), F (Chattopadhyay et al 2001), G (Pope et al 2010), H (Riipinen et al 2007), I (Saleh et al 2009), J (Saleh et al 2010), K (Salo et al 2010), and L (Soonsin et al 2010). Kuwata et al (2012) 0 the limited volatilization observed.…”
Section: Tablementioning
confidence: 99%